Approximation of the socio-cultural importance of the Moriche palm tree (Mauritia fleuxuosa L.F.) in the Wacoyo indigenous community (Sikuani) in the municipality of Puerto Gaitán, Colombia - Marco A. Torres-Mora (Orinoquia, 2015)
The Moriche palm tree ( Mauritia flexuosa L.F) is a natural resource that offers a range of resources, such as insect larvae, raw materials for beverages and fibers; as a result, local communities take advantage of these trees for the economic income and welfare of their families. For example, the Sikuani people, who belong to the communities that integrate the “Resguardo” Wacoyo, own one of the best-preserved morichales (ecosystems in which the palm is abundant) of the Puerto Gaitán municipality of Meta. The aim of this study was to understand the exploitation methods, usage and products that are associated with the moriche palm tree in the communities of the Sikuani people who inhabit the “resguardo.” It was found that, through the use of the leaves, shoots and fruits, these communities obtain raw materials for making crafts and a fermented beverage. The forms of exploitation have a low impact on the natural environment because a period of recovery time is allotted for the palm trees. Finally, it can be concluded that the Sikuani people seek to safeguard their morichales based on their ancestral knowledge about the use and management of this type of resource.